Triple Techniques to Relieve Critical-time Stress of Cotton Plants to Maximize Bio-resource Output and Farm Returns - Narayanan, S. S.; Maiti, R. K.; Vidyasagar, P. (International Journal of Bio-resource and Stress Management, 2010)
Cotton is grown under irrigated as well as fully rain-fed conditions. However, prolonged water stress at boll maturity and fiber development stage often causes yield reduction and produces poor quality fibers. Besides, heavy infestation by weeds also cause crop loss with adverse effect on fiber and seed quality. The third stress is caused by severe pest attack like bollworms. Transgenic Bollgard (BG) cotton provides protection from bollworms by providing a self-defense mechanism to the cotton plants. However, it is not easy to grow Bt-hybrid cotton, preferably BG-II versions. The paper recommends triple techniques to relieve critical-time stress of cotton plants to maximize bio-resource output and farm returns. Triple techniques include circumventing critical moisture stress period on cessation of rainfall, effectively eliminating severe stress caused by weed competition, and use of BG-II version against bollworms based on research-based recommendations.